Sex, gender and the carceral: Female staff experiences of working in forensic care with sexual offenders. (July 2018) - Mercer, Dave; Perkins, Elizabeth
Abstract: English high-secure hospitals have contained individuals deemed mentally disordered, and dangerous, since the mid-nineteenth century. With the development of gender sensitive services female patients have been moved out of these institutions into smaller secure settings. Female staff continue to work in high secure hospitals, but are often in a minority in these services. Little is known about how female staff experience the everyday world of work. This paper is based on in-depth interviews with female nurses employed in a unit caring for detained male sexual offenders with a diagnosis of personality disorder. It forms part of a much larger discourse-analytic study of nine patients, with a history of sexual offending, and eighteen mental health nurses, which focused on talk about pornography and criminality. The findings from this project have been previously reported in Mercer and Perkins (2014). This paper demonstrates how patriarchy remains an enduring cultural characteristic of caring for men detained under theMental Health Act (1983, 2007) because of sexually violent crimes against women and children. It textures the ward environment and the relationships between people who work within it, constructing women as 'outsiders' and producing a masculine culture which leaves female staff feeling vulnerable and at risk. The analytic focus of the paper is concerned with exploring how women experience working in the male-dominated environment of a high-security Personality Disorder Unit (PDU). Three discursive repertoires are identified: the institutional space as male, the impact of working with men detained as a result of sexual offending, and the construction of therapeutic work as a 'job for the boys'. In this world, female staff, as a product of their gender, constructed themselves both as at risk and inviting risk.